1995
DOI: 10.1111/j.2042-7158.1995.tb05797.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Policosanol on Lipofundin-induced Atherosclerotic Lesions in Rats

Abstract: Policosanol is a mixture of higher aliphatic alcohols isolated from sugar cane wax, showing cholesterol-lowering effects and preventing the development of lipofundin-induced lesions in New Zealand rabbits. This study was conducted to determine whether policosanol orally administered to rats also protects against the development of lipofundin-induced atherosclerotic lesions. Fifty four male Wistar rats were randomly distributed amongst a negative control group, a positive control group intravenously injected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that policosanol prevents the onset of spontaneous atherosclerotic lesions in Macaca arctoides monkeys (19) and in lipofundininduced lesions in rabbits and rats (20)(21)(22). The physiological basis of this action may be related not only to the cholesterol-lowering A B C effects of policosanol, but also to the reduction of thromboxane A 2 (TxA 2 ) and to the increase in prostacyclin levels induced by policosanol (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that policosanol prevents the onset of spontaneous atherosclerotic lesions in Macaca arctoides monkeys (19) and in lipofundininduced lesions in rabbits and rats (20)(21)(22). The physiological basis of this action may be related not only to the cholesterol-lowering A B C effects of policosanol, but also to the reduction of thromboxane A 2 (TxA 2 ) and to the increase in prostacyclin levels induced by policosanol (30).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous experiments have revealed that policosanol prevents the development of spontaneous lesions in Macaca arctoides monkeys (19) and in lesions induced by lipofundin in rabbits and rats (20)(21)(22). To date, the effect of policosanol on the atherosclerotic lesions induced in rabbits by a cholesterol-rich diet has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was repeated daily for 7 days. Lipofundin (2 mL/kg) was then intravenously administered for 8 consecutive days [10]. The third group received a daily dose of normal saline for 7 days before the administration of the same dose (2 mL/kg) of Lipofundin.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…While statins have been shown to induce a slight increase in hepatic enzymes in humans (Castano et al, 2002c;Castano et al, 2003b), SCP mixtures did not affect these parameters and were even seen to play a protective role against liver and endothelial (Noa et al, 1997) damage, atherosclerotic lesions (Noa et al, 1995) as well as myocardial necrosis, delaying the evolution of infarction in rats. Rodriguez et al tested peri-and post-natal toxicity and teratogenicity of policosanols in rats and rabbits in studies involving doses of 5, 50, 500 and 1000 mg/kg/day of policosanols during pregnancy and after parturition.…”
Section: Composition and Metabolism Of Policosanol Mixturesmentioning
confidence: 97%